2018
DOI: 10.1038/s41388-017-0040-z
|View full text |Cite
|
Sign up to set email alerts
|

PAX8 activates a p53-p21-dependent pro-proliferative effect in high grade serous ovarian carcinoma

Abstract: High grade serous carcinoma (HGSC) is the most common subtype of ovarian cancer and it is now widely accepted that this disease often originates from the fallopian tube epithelium. PAX8 is a fallopian tube lineage marker with an essential role in embryonal female genital tract development. In the adult fallopian tube, PAX8 is expressed in the fallopian tube secretory epithelial cell (FTSEC) and its expression is maintained through the process of FTSEC transformation to HGSC. We now report that PAX8 has a pro-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 59 publications
1
28
0
Order By: Relevance
“…More importantly, we found that PAX8 silencing inhibited the proliferation and clonogencity of HCC cells in vitro and the growth of implanted HCC xenografts in vivo. Furthermore, PAX8 silencing induced HCC cell cycle arrest in S phase by downregulating E2F1, RB and P53 expression in HCC cells, consistent with previous reports [16,33]. Therefore, PAX8 may be a new biomarker and therapeutic target for prognosis and intervention of HCC.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…More importantly, we found that PAX8 silencing inhibited the proliferation and clonogencity of HCC cells in vitro and the growth of implanted HCC xenografts in vivo. Furthermore, PAX8 silencing induced HCC cell cycle arrest in S phase by downregulating E2F1, RB and P53 expression in HCC cells, consistent with previous reports [16,33]. Therefore, PAX8 may be a new biomarker and therapeutic target for prognosis and intervention of HCC.…”
Section: Discussionsupporting
confidence: 89%
“…PAX8 is important for embryogenesis, and morphogenesis of the thyroid and kidney [14]. Furthermore, PAX8 expression is upregulated in several types of cancers and is a valuable biomarker for diagnosis of glioma, ovarian carcinoma, gastric cancer and others [15][16][17]. A recent study has reported that single nuclear polymorphism of the PAX8 gene is associated with prognosis of Chinese patients with HCC [18].…”
Section: Introductionmentioning
confidence: 99%
“…The sustained expression of PAX8 in the adult FTSEC and in nearly all HGSOCs (16), previously led us to use the PAX8 promoter to develop a genetically engineered mouse model of HGSOC (17,18). Knockdown of PAX8 in ovarian cancer cells leads to apoptosis (19)(20)(21) supporting a definitive role for PAX8 in ovarian cancer growth and progression. However, it remains unclear how PAX8 drives the development of the Mullerian reproductive tract or how it supports neoplastic growth.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the new protein coding associations involved alternative promoters of known cancer genes that were not represented in the hg19 version, such as epigenetic regulation of the PAX8 gene in a subset of CHOL tumors ( Figures 3D and 3E). While PAX8 activity has been associated with cancers originating from the thyroid, M€ ullerian, and renal tracts (Ghannam-Shahbari et al, 2018;Laury et al, 2011), neither this new isoform nor upregulation in cholangiocarcinoma have been previously described. In Supplemental Methods, we describe additional resources available at the GDC that can aid users in analyzing TCGA methylation data: (1) improved HM27/HM450 probe annotation (Zhou et al, 2017) and data generation pipelines (Zhou et al, 2018b), which are planned to become the default processing version in a forthcoming GDC data release; and Whole-Genome Bisulfite Sequence data for 47 TCGA samples (Zhou et al, 2018a), which can be used to investigate whole-genome methylation patterns.…”
Section: Dna Methylationmentioning
confidence: 97%